Quantifying on-water performance in rowing: A perspective on current challenges and future directions - Binnie, M. J.; Astridge, D.; Watts, S. P.; Goods, P. S. R.; Rice, A. J.; Peeling, P. (Frontiers in Sports and Active Living, 2023)
Winning times at benchmark international rowing competitions (Olympic Games and World Championships) are known to vary greatly between venues, based on environmental conditions and the strength of the field. Further variability in boat speed for any given effort is found in the training environment, with less controlled conditions (i.e., water flow, non-buoyed courses), fewer world class competitors, and the implementation of non-race specific effort distances and intensities. This combination of external factors makes it difficult for coaches and practitioners to contextualise the performance underpinning boat speed or race results on any given day. Currently, a variety of approaches are referenced in the literature and used in practice to quantify this underpinning performance time or boat speed, however, no clear consensus exists. The use of relative performance (i.e., time compared to other competitors), accounting for influence of the weather (i.e., wind and water temperature), and the novel application of instrumented boats (with power instrumentation) have been suggested as potential methods to improve our understanding of on-water rowing speeds. Accordingly, this perspective article will discuss some of these approaches from recent literature, whilst also sharing experience from current practice in the elite environment, to further stimulate discussion and help guide future research.